Immunization Vaccine Adjuvant Delivery System and Strategies - Wang, Ning; Wang, Ting (IntechOpen, 2018)
Immunization plays a key role in maintaining human health and each year, saves millions of lives from lethal pathogens and other fatal diseases in the most economical way, thanks to the advanced development of model vaccines. Subunit vaccines are regarded as a safer product than the whole microbe based-conventional vaccines and can be entrapped in various nanocarriers to form a vaccine adjuvant-delivery system (VADS) able to further boost their immunostimulatory activity. In this book, six groups of authors introduce immunization advances in VADSs designed for infection prophylaxis and cancer immunotherapy, problems and their resolution in both human and poultry immunization, and also, the mathematical model for assay of the basic immunization problem (BIP) understood from a finance point of view.